A Customer Satisfaction Levels Between Cab Service Provider’s UBER and OLA in the Ahmedabad - Dhruvraj Rajpurohit; Nagpal Makwana; Jignesh Vidani (MultiTech Publisher, 2024)
This research examines customer satisfaction between Uber and Ola in Ahmedabad, India, focusing on factors such as age, app usability, safety perceptions, pricing fairness, and recommendation likelihood. Using chi-square testing, the study finds that age does not significantly influence service preferences, app usability, or pricing perceptions, with only weak associations observed, However, safety perceptions are particularly important for older customers, suggesting a need for improved communication of safety features by both companies. No significant preference for Uber or Ola emerged across age groups, with both companies equally rated for app usability and pricing. The study recommends that Uber and Ola enhance safety measures, improve pricing transparency, and invest in personalized marketing to boost customer satisfaction and loyalty